Pengaruh Komunikasi, Lingkungan Kerja dan Pengembangan Pegawai Terhadap Motivasi Kerja Pegawai Dikantor Camat Bendahara Kabupaten Aceh Tamiang - Fakhrurrazi Syamsuyar; Mara Timbul Daulay; Amin Saragih; Mukhtar Hadi; M. Ilham Malik; Eddi Suprayitno (Journal of Trends Economics and Accounting Research, 2023)
The aims of this study are: (1) To determine the effect of communication on employee work motivation at the Kantor Camat Bendahara Kabupaten Aceh Tamiang. (2) To determine the effect of the work environment on the motivation of employees at the Kantor Camat Bendahara Kabupaten Aceh Tamiang. (3) To determine the effect of employee development on employee work motivation at the Kantor Camat Bendahara Kabupaten Aceh Tamiang. (4) To determine the effect of communication, work environment and employee development on employee work motivation at the Kantor Camat Bendahara Kabupaten Aceh Tamiang. This research was conducted at the Kantor Camat Bendahara Kabupaten Aceh Tamiang. With a population of 38 people. The sample in the study was determined by total sampling technique, so that the sample used was the entire population, which was 38 people. Data collection techniques used non-test methods, with questionnaire research instruments and library studies. Data analysis using SPSS with descriptive analysis and regression analysis. From the results of the analysis obtained: (1) There is a positive and significant influence of the communication variable on the work motivation of employees at the Kantor Camat Bendahara Kabupaten Aceh Tamiang. (2) There is no positive and significant effect of the work environment variable on the work motivation of employees at the Kantor Camat Bendahara Kabupaten Aceh Tamiang. (3) There is an effect of employee development on employee work motivation at the Kantor Camat Bendahara Kabupaten Aceh Tamiang. (4) There is an effect of communication, work environment and employee development on employee work motivation at the Kantor Camat Bendahara Kabupaten Aceh Tamiang.